Financial crisis and opportunities in global capital markets under the influence of the COVID-19 pandemic - Čorko, Dragica (Crisis Management Days, 2025)
Introduction The pandemic caused by the Covid-19 virus, in addition to its health consequences, has left behind the foundation for the creation of other crises. Job losses due to the suspension of many businesses and a double-digit inflation rate with indications of a possible global recession are a sure path to a financial crisis. Measures to mitigate and combat the consequences of the global pandemic have triggered difficulties and unpleasant challenges for world economies, the financial system and capital markets. Most have felt the negative consequences of financial disturbance, but for individuals, the market crisis has served as an opportunity to realize an opportunity and increase private financial assets. Methodology The following work is based on observing the sequence of events and correlating measures related to mitigating the consequences of the global pandemic caused by the Covid-19 virus and recording the movements of relevant investment classes on the capital market and global economic indicators. The observed period is from the beginning of the virus outbreak and indications of the pandemic; the beginning of 2020, up to and final 2023 and indications of recovery of the financial and capital markets. There is a stronger focus on 2022, which can be called a challenging year, or even a year marked by the global financial crisis. Aim and purpose of the work The global progress and development of modern society, along with life improvement for the population, unavoidably brings with it the increased occurrence of crisis situations and the confrontation with some new ones. The global pandemic caused by the Covid-19 virus and the consequences it left behind have crept into every corner and segment of the modern world. Lockdown, or global quarantine, stopped supply chains of goods around the world, temporarily suspended many jobs and slowed down economic growth. The funds needed to mitigate the consequences of the virus were secured through bonds, states borrowed, and a critical mass of money was created. Inflation, the sudden rise in the prices of products and services was inevitable, which further impoverishes the global population, which is already psychologically shaken by the health crisis. The monetary measures of the Central Banks to lower the double-digit inflation rate to an acceptable level are increasing the price of money by raising interest rates, which in turn further reduces the purchasing power of the population and slows down economic investments. Such measures can also lead to regional or global recessions. However, with all the challenges and extremely negative returns on investments through capital markets; stocks, bonds, commodities, investment funds throughout 2022, the wealthier and more financially literate have used the stock market crash and the crisis to further enrich themselves. In the context of crisis management, there is not enough talk about financial crises, which are becoming more frequent, and the concepts and movements from the capital market are not sufficiently known. The aim of this paper is to show how one crisis triggers another crisis situation of a completely different context, and in particular to encourage more thinking and possibilities for managing financial crises in global capital markets in the context of crisis management. Classic banking and savings are in the front of the door of the past, and investments in various asset classes of investment products on capital markets are the finances of the future. Media interest and the tendency to exaggerate the negative is an additional reason for the necessity of raising financial literacy in general. In the context of crisis management, it is also necessary to understand how to recognize real crises from potential or media-induced ones, and to adopt ways to reduce additional negative consequences.